2010
DOI: 10.4103/0974-2948.71051
|View full text |Cite
|
Sign up to set email alerts
|

Natural dyes versus lysochrome dyes in cheiloscopy: A comparative evaluation

Abstract: Cheiloscopy is the study of lip prints. Lip prints are genotypically determined and are unique, and stable. At the site of crime, lip prints can be either visible or latent. To develop lip prints for study purpose various chemicals such as lysochrome dyes, fluorescent dyes, etc. are available which are very expensive. Vermilion (Sindoor used by married Indian women) and indigo dye (fabric whitener) are readily available, naturally derived, and cost-effective reagents available in India.Objective:To compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…(2010)[ 13 ] proved that fluorescent dyes could give results comparable with lysochrome dyes such as Sudan Black B. Singh et al . (2010),[ 14 ] conducted a similar study using Sudan Black B, on bone china cups, and satin and other cotton fabrics, from which they concluded that natural dyes such as vermilion and indigo gave results comparable to Sudan Black B in developing latent lip prints. In our study we have made use of the most efficacious lysochrome dye, Sudan black B [as per Navarro et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2010)[ 13 ] proved that fluorescent dyes could give results comparable with lysochrome dyes such as Sudan Black B. Singh et al . (2010),[ 14 ] conducted a similar study using Sudan Black B, on bone china cups, and satin and other cotton fabrics, from which they concluded that natural dyes such as vermilion and indigo gave results comparable to Sudan Black B in developing latent lip prints. In our study we have made use of the most efficacious lysochrome dye, Sudan black B [as per Navarro et al .…”
Section: Discussionmentioning
confidence: 99%
“…Oil Red O is a fat-soluble dye that stains neutral triglycerides and lipids [27]. Intracellular triglyceride droplets of hADMSCs were stained with Oil Red O solution on day 4, 10, and 21.…”
Section: Oil Red O Stainingmentioning
confidence: 99%
“…Synthetic substances such as aluminum powder, silver metallic or lead carbonate powder have also been used to develop latent lip prints 4 . The lysosome dyes (eg, Sudan III, Sudan Black and Oil Red O) dissolve in lipids produced from the sebaceous glands of the lips 6 . These dyes effective stain both non‐porous and porous surfaces 6 …”
Section: Introductionmentioning
confidence: 99%
“…The lysosome dyes (eg, Sudan III, Sudan Black and Oil Red O) dissolve in lipids produced from the sebaceous glands of the lips 6 . These dyes effective stain both non‐porous and porous surfaces 6 …”
Section: Introductionmentioning
confidence: 99%